The Importance of Diagnosis and Specialized Treatment in Merkel Cell Carcinoma: Case Report in a Young Healthy Woman, Literature Review and Brief Update on Approach (Global Journal of Medical Research, 2020)
Merkel Cell Carcinoma (MCC) is extremely rare and aggressive, with an overall survival of 40% in 5 years. The non-oncological physician has large difficulty about the correct approach of this pathology. We report the sixth case of MCC in a young healthy patient (woman, 19 years old) described in the medical literature, who was treated twice for sebaceous cyst, evolved with local disease progression, needed a larger resection and, after adjuvant therapy, remains no tumor recurrence. Despite being an extremely rare neoplasm, therapeutics should not be underestimated by non-oncological physician because this cancer is too aggressive, and the correct oncological approach could result in increased progression-free survival for these patients.
Keywords: merkel cell carcinoma; young; healthy